Cancer Specific CAIX‐Targeting Supramolecular Lysosome‐Targeting Chimeras (Supra‐LYTAC) for Targeted Protein Degradation - Dohyun Kim; Gyeongseok Yang; Chaelyeong Lim; Gaeun Park; Jaemo Lee; Youjung Sim; Ja‐Hyoung Ryu (Advanced Science)
Abstract Recently, targeted protein degradation (TPD) strategies have emerged as a promising solution to tackle undruggable proteins. While most TPD strategies target intracellular proteins, limited options exist for targeting extracellular or membrane proteins. Herein, cancer specific carbonic anhydrase IX (CAIX)‐targeting supramolecular nanofibrous lysosome‐targeting chimeras (Supra‐LYTAC) is reported. Two self‐assembling amphiphilic peptides are synthesized: one that interacts with the protein of interest (POI), and another that mediates lysosomal endocytosis by targeting a cancer‐specific enzyme. Notably, these two peptides co‐assemble into nanofibers capable of targeting cancer cells in a spatiotemporal manner. Through dynamic and multivalent binding, a ternary complex form (supramolecular chimeric nanostructure; CAIX‐nanofiber‐POI), which undergoes internalization into lysosomes where the POI is degraded through lysosomal catalytic activity. This study demonstrates the potential of supramolecular approaches to expand the scope of LYTAC technology, offering new opportunities for designing TPD strategies in the future.